Efficient production of 5-ethoxymethylfurfural from 5-hydroxymethylfurfural and carbohydrates over lewis/brønsted hybrid magnetic dendritic fibrous silica core-shell catalyst. (January 2022) - Hafizi, Hamid; Walker, Gavin; Collins, Maurice N.
Abstract: In the present work, a series of Brønsted and Lewis hybrid, magnetic, dendritic fibrous silica microsphere core shell particles with an open and easily accessible mesopore channels as the catalyst supports (Fe3 O4 @SiO2 @KCC-1) were prepared, impregnated with aluminum (10 wt%) followed by encapsulation of different loadings of tungstophosphoric acid (PTA) from 10 to 40 wt% into mesoporous channels of fibrous silica shell (Fe3 O4 @SiO2 @KCC-1/Al10 /PTAx ). They are utilised for the efficient and clean production of biomass-derived liquid fuel 5-ethoxymethylfurfural (EMF) through direct etherification of hydroxymethylfurfural (HMF) and one-pot conversion of fructose and other carbohydrates. High EMF yields of 93.1%, 62.2%, 23.9%, and 21.4% were obtained, when HMF, fructose, sorbose, and sucrose were subjected as substrate, respectively. These catalysts were characterised by XRD, py-FTIR, TGA, N2 -physisorption, SEM and TEM-EDX mapping. Importantly, the catalyst could be reused at least four times almost without a significant loss of activity. Graphical abstract: Image 1